2012
DOI: 10.1111/j.1440-169x.2011.01308.x
|View full text |Cite
|
Sign up to set email alerts
|

Tudor domain‐containing proteins of Drosophila melanogaster

Abstract: Tudor domain-containing proteins (Tudor proteins), which recognize and bind to methyl-arginine ⁄ lysine residues, play important roles in diverse epigenetics, gene expression and the regulation of various small RNAs. Using the complete set of 23 Tudor proteins from Drosophila, together with the available functional information, we propose a putative link for different types of Tudor domains (histone-binding, SMN and SND1) and the four functional groups of Tudor proteins (Group 1, binding the methyl-lysine ⁄ ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 62 publications
1
18
0
1
Order By: Relevance
“…In mammals, 12 members of the TDRD protein family have been identified since Drosophila Tudor proteins were discovered [18,20,22,23,24,29,30,36,37,38]. We also demonstrated that our newly identified Tdrd12 is most homologous to mouse and human TDRD12 among the 12 TDRD family members.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In mammals, 12 members of the TDRD protein family have been identified since Drosophila Tudor proteins were discovered [18,20,22,23,24,29,30,36,37,38]. We also demonstrated that our newly identified Tdrd12 is most homologous to mouse and human TDRD12 among the 12 TDRD family members.…”
Section: Discussionsupporting
confidence: 59%
“…Among PIWI-interacting proteins, Tdrd family proteins have been revealed as important molecules for piRNA biogenesis. Twelve members of TDRD family proteins have been identified in mice since the Drosophila Tudor protein was discovered [20,21]. They are mainly involved in germ cell development [19].…”
Section: Introductionmentioning
confidence: 99%
“…tudor is one of 23 Tudor domain-containing proteins in Drosophila (Ying and Chen, 2012), but there is no evidence that loss of function of other Tudor domain-containing genes have grandchildless phenotypes in Drosophila (Handler et al, 2011; Pek et al, 2012). We therefore focus only on the expression and function of the orthologue of Drosophila tudor (CG9450).…”
Section: Resultsmentioning
confidence: 99%
“…These genes coded for proteins with regulative TUDOR, NYN or BTB/POZ domains (Anantharaman & Aravind ; Misra et al . ; Ying & Chen ). We found that members of these putative regulatory families were constitutively downregulated upon adaptation (Table S2, Supporting information).…”
Section: Discussionmentioning
confidence: 99%